Examination of two different proteasome inhibitors in reactivating mutant human cystathionine β-synthase in mice - Gupta, Sapna; Lee, Hyung-Ok; Wang, Liqun; Kruger, Warren D. (PLOS ONE, 2023)
Classic homocystinuria is an inborn error of metabolism caused mainly by missense mutations leading to misfolded and/or unstable human cystathionine β-synthase (CBS) protein, causing the accumulation of excess total homocysteine (tHcy) in tissues. Previously, it has been shown that certain missense containing human CBS proteins can be functionally rescued in mouse models of CBS deficiency by treatment with proteasome inhibitors. The rescue by proteasome inhibitors is thought to work both by inhibiting the degradation of misfolded CBS protein and by inducing the levels of heat-shock chaperone proteins in the liver. Here we examine the effectiveness of two FDA approved protease inhibitors, carfilzomib and bortezomib, on various transgenic mouse models of human CBS deficiency. Our results show that although both drugs are effective in inducing the liver chaperone proteins Hsp70 and Hsp27, and are effective in inhibiting proteasome function, bortezomib was somewhat more robust in restoring the mutant CBS function. Moreover, there was no significant correlation between proteasome inhibition and CBS activity, suggesting that some of bortezomib’s effects are via other mechanisms. We also test the use of low-doses of bortezomib and carfilzomib on various mouse models for extended periods of time and find that while low-doses are less toxic, they are also less effective at restoring CBS function. Overall, these results show that while restoration of mutant CBS function is possible with proteasome inhibitors, the exact mechanism is complicated and it will likely be too toxic for long-term patient treatment.